Desain Relayout Gudang dengan Metode Weighted Distance untuk Meminimasi Travel Time - Firmansyah, Adi; Lukmandono (TALENTA Publisher, 2020)
PT IJS is a company engaged in logistics services in the Perak area of ​​Surabaya. PT IJS was founded in 1984 when the need for container depots was urgently needed around the Tanjung Tanjung port area to unravel the shipping queues and shorten licensing. One of the services provided by PT IJS is bounded warehouse rental services. Bounded warehouse owned by PT IJS is currently not able to provide maximum service because there are still many late deliveries which do not result in the sending of goods to the port and there is a closing time that is detrimental to the customer. The length of the delivery process is due to several factors, one of which is a less effective company layout. Travel time is the time required for a vehicle to carry out goods loading activities at PT. IJS from arrival to exit company. Based on travel time calculations when using the initial layout, the travel time value of T = 2002 seconds. The weighted-distance method is a mathematical model used to evaluate the layout based on proximity factors. The design of the relayout design using the weighted-distance method produces alternative layouts that produce shorter travel time calculations, alternative layout with T = 1849 seconds